Understanding the digital customer journey of Indonesian full service restaurants in sourcing food suppliers - Albert Gianta Margono; Atik Aprianingsih (International Journal Labs, 2024)
This study aims to provide a comprehensive understanding of the needs, preferences, and behaviors of its target market in the Indonesian full-service restaurant (FSR) sector. Firstly, it seeks to map the customer journey of FSRs in the food supplies purchasing process, identifying key touchpoints, brand awareness levels, information sources, and factors influencing brand choice. Secondly, it evaluates the effectiveness of various digital marketing channels, such as social media advertising, search engine marketing, and email marketing, by analyzing cost-per-lead and conversion rates to identify the most efficient channels for acquiring new FSR customers for PT MBI. Finally, the research intends to develop a data-driven digital marketing strategy that optimizes customer interactions, enhance brand visibility, and improve lead generation at each decision-making stage to drive sales conversions and increase customer lifetime value. The results of this study show that the current focus of PTXYZin the FSR segment lies between two segments: Relationship-Driven Traditionalists and Hybrid Decision-Makers.